Optimizing Agriculture through Digital Transformation: The Role of BUMDes in Haurngombong Village, Sumedang District - Taufik Taufikurahman; Oktofa Yudha Sudrajad; Mochamad Apri; RR. Deby A Rizkyani; Rizka Purnamawati; Tetep Ginanjar; Zelika R Noviana; Nanda Shofiyah Ulfa (Center for Rural Areas Empowerment (P2D), Institut Teknologi Bandung, 2025)
The primary challenge faced by farmers in Haurngombong Village is their low bargaining power in marketing agricultural produce, which is attributed to limited access to market information, capital, and distribution channels. To address this, the Center for Rural Empowerment (P2D), along with the Village-Owned Enterprise (BUMDes) Berbudi, initiated the Digital Platform Utilization Program in Haurngombong Village to strengthen the position of farmers as producers. This program aims to assist farmers in distributing and marketing their agricultural products through a digital platform, enabling them to determine a fairer selling price and expand their market network. Additionally, the program serves as a collaborative platform for farmer communities, such as the Women Farmers Group, and MSEs actors in the surrounding village area. The empowerment activities employ the Participatory Learning Activity (PLA) method, emphasizing participatory learning through lectures, discussions, and direct practice (learning by doing). The activities included initial socialization, a Focus Group Discussion (FGD), website design creation, product information collection, digital marketing training, and daily transaction recording. The program also promotes the active role of BUMDes Berbudi in assisting with product marketing, including participation in bazaars like Milangkala Desa Haurngombong and Jatifest 2023 at the ITB Jatinangor Campus. Although the program has yielded positive impacts, constraints remain, primarily related to farmers' limited access to technological devices and internet network. Further study is required to understand the correlation between the pattern of human resource (HR) utilization in agricultural activities and the effectiveness of utilizing and digitally marketing agricultural products.